Strategy Formulation and Implementation of UD Suwardi, Areal Estate Company in Bekasi - Sadewo, Adnan Faris; Wandebori, Harimukti (Journal of Business and Management, 2013)
The main theme of this research is Strategic Management and focus on finding a Strategy Formulation and Implementation of UD Suwardi, a real estate company in Bekasi. Since the first tool of this research is Environmental Scanning Analysis, it explains that strategy formulation and implementation can be done after scanning both the external environment, to identify possible opportunities and threats, and the internal environment, for strengths and weaknesses. It also explains that these identifications are purposed to find strategic factors that will determine the future of the company. The researcher uses Sustainability Issues, PEST Analysis, and Porter 5 Forces as the observation tools for external environment and Business Models, Resources-Capabilities-Core Competencies, and Value Chain Analysis as the scanning tools for internal environment. After strategic factors are identified, the researcher use SWOT Analysis to identify the company’s distinctive competencies and SFAS Matrix to know and measure how well a particular company’s management responds to these strategic factors in light of the perceived importance of these factors to the company. From the calculation of EFAS and IFAS Matrix, the researcher uses the quarrel between strength-weakness points and opportunities-threats points as the criterion of company’s position at Corporate Strategy Matrix. By having 3.48 points of EFAS and 3.19 of IFAS, the company is considered as an average firm which has already had sufficient basic to compete in its industry and currently positioned at Growth Stage. Prior to such result and the consideration of real estate developer’s rivalry pattern, the researcher suggests the company to apply Directional Growth Strategy and Differentiation Strategy to acquire key employees for the company and to produce products and services that customer’s perceive different in ways that are important to them . The researcher also uses TOWS Matrix to generate alternative strategies that decision makers of the company might not otherwise have considered for the development of the company, Value-Creating Activities to give specific pictures of what each functional division should do, and Financial Projection as its benchmark of development in the following years.  Last but not least, a functional organizational structure is formed to accommodate the company to implement Differentiation Strategy and its employees to apply development-oriented culture.  Keywords: Sustainability Issues, PEST Analysis, Porter 5 Forces, Business Models, Value Chain Analysis, SWOT Analysis, EFAS Matrix, IFAS Matrix, Corporate Strategy Matrix, Directional Growth Strategy, Differentiation Strategy, TOWS Matrix, Environmental Scanning Analysis--------------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.